Understanding organ donation : applied behavioral science perspectives - Siegel, Jason T.; Alvaro, Eusebio M.; Claremont Symposium on Applied Social Psychology 2007) (Chichester, U.K. ; Malden, MA : Wiley-Blackwell, 2010)
This highly important book introduces the realm of organ donation, providing an overview of the current situation, highlighting the challenges, summarizing past research, and providing guidance for future research.: The first book to bridge the gap between applied research and the social and behavioral issues surrounding organ donation; An impressive collection of contributors from a range of both practitioners and scientists actively working in the field; Provides a concrete example of how evidence-based research and theory can be applied with real-world value; Explores future directions of.
Home Care Association of Louisiana (HCLA) Donate Life workplace partnership for organ and tissue donation / Carolyn C. Johnson & Larry S. Webber -- Promoting organ donation through college student campaigns / Thomas Hugh Feeley [and others] -- Take time to talk : improving communication between recovery professionals and funeral directors / Catherine Paykin, Gigi Politoski, and Linda Singleton-Driscoll -- The challenges of conducting and evaluating organ donation campaigns / Susan E. Morgan -- Community organizations and applied research : project initiation, implementation, and dealing with those applied researchers / Sara Pace Jones and David Bosch -- Evaluating the effects of community-based health interventions : seeking impact and saving lives via organ and tissue donation promotion efforts / Robert L. Fischer -- The value of qualitative studies of interpersonal conversations about health topics : a study of family discussions of organ donation and illustrations / Anita Pomerantz -- Ethically and effectively advancing living donation : how should it be done? / Amy D. Waterman and James R. Rodrigue -- A dawning recognition of factors for increasing donor registration : the IIFF model / Jason T. Siegel, Eusebio M. Alvaro, and Zachary P. Hohman -- There's nothing so practical : theoretical translations and organ donation / William D. Crano.
Includes bibliographical references and indexes.
Print version record.
Keywords: Donation of organs, tissues, etc. -- Psychological aspects; Clinical health psychology; Tissue and Organ Procurement; Cultural Diversity; Health promotion; Program Development; Program evaluation; Tissue Donors -- psychology; Electronic books; Electronic books